Students Writing Ability Test According To CEFR Standards using Argumentative Text - Pasaribu, Ronal Rendy Yuleo; Pratama, Hendi (ITScience (Information Technology and Science), 2026)
This study examines the extent of 12th-grade students' writing skills by evaluating their performance against the CEFR standards. The primary objective was to identify whether students in their final year of secondary school can achieve B2 proficiency in writing argumentative texts. The study addresses a critical research gap by focusing on 12th-grade students as a transitional group, a population often underrepresented in university-level studies. Using qualitative fieldwork methods, data were collected through questionnaires to explore the underlying factors influencing writing success. The theoretical framework was based on the Common European Framework of Reference for Languages (CEFR) scales, and the analysis focused on components such as thesis clarity, organization, and language use. Findings indicated that although some students demonstrated strong content development, many still struggled with the linguistic mechanics necessary for B2 consistency. Quantitative analysis revealed significant proficiency gaps, with twenty-three respondents performing at the B1 level and only four students reaching the B2 threshold. Diagnostic profiles identified limited academic vocabulary and a fear of grammatical errors as key factors hindering students' ability to develop complex argumentative structures. By identifying these specific barriers, this study provides pedagogical insights for educators to refine their teaching strategies and align classroom assessments with international benchmarks to support students in their transition to higher education. Ultimately, the results establish a valuable diagnostic profile for future curriculum development and targeted writing interventions.